A Randomized Trial of Bictegravir or Dolutegravir with Emtricitabine and Tenofovir Alafenamide (F/TAF) Followed by Open Label Switch to Bictegravir/F/TAF Fixed Dose Combination. (4th October 2017) - Sax, Paul E; Dejesus, Edwin; Crofoot, Gordon; Ward, Douglas; Benson, Paul; Wei, Lilian; White, Kirsten; Collins, Sean; Martin, Hal; Cheng, Andrew; Quirk, Erin
Abstract: Background: Integrase strand transfer inhibitors (INSTIs) are widely recommended for initial HIV-1 treatment. Bictegravir (BIC, B) is a novel, once-daily INSTI with potent antiviral activity being developed in coformulation with emtricitabine and tenofovir alafenamide (F/TAF). Methods: In this Phase 2 study, treatment naïve, HIV-infected adults were randomized 2:1 to receive blinded treatment with BIC or dolutegravir (DTG) coadministered with open label F/TAF (200/25 mg). After all participants completed 48 weeks, they were unblinded and switched to a single fixed-dose combination tablet of B/F/TAF 50/200/25 mg. The proportion of participants with HIV-1 RNA <50 copies/mL (c/mL) was assessed at Week (W) 24 and W48 of the blinded phase and 12 weeks after switching to open label B/F/TAF (W72). Results: Of 98 participants enrolled in the blinded treatment phase, 65 were randomized to BIC+F/TAF and 33 to DTG+F/TAF. Most were male, had asymptomatic HIV infection, with median HIV-1 RNA 4.4–4.5 log10 c/mL. The proportion of subjects with HIV-1 RNA <50 c/mL at W24 was 97% for the BIC arm and 94% for the DTG arm, and at W48 was 97% and 91%, respectively (Table). All 92 participants who completed the blinded phase were switched to B/F/TAF at W60. At W72 or 12 weeks after switching to open-label B/F/TAF, 99% (91/92) maintained HIV-1 RNA <50 c/mL (98% prior BIC arm [ N = 62]; 100% prior DTG arm [ N = 30]) and one individual withdrew prior to the analysis. No viral resistance was detected in participants treated with BIC. No participants discontinued open label B/F/TAF due to an adverse event, there were no treatment-related serious adverse events and no deaths. One individual on BIC previously discontinued due to an adverse event of urticaria following the W24 visit. Conclusion: All participants switched from DTG+F/TAF to open-label B/F/TAF maintained virologic suppression, with none discontinuing due to adverse events. During 72 weeks of follow-up, no treatment-emergent resistance to any components was detected in participants taking B/F/TAF. B/F/TAF demonstrated durable virologic suppression in naïve patients through W72 and was safe and effective after switching from DTG + F/TAF, further study in treatment naïve and experienced populations is warranted. Disclosures: P. E. Sax, Gilead: Consultant and Investigator, Consulting fee, Research grant and Research support; BMS: Consultant and Investigator, Consulting fee, Research grant and Research support; GlaxoSmithKline/ViiV: Consultant and Investigator, Consulting fee, Research grant and Research support; AbbVie: Consultant, Consulting fee; Janssen: Consultant, Consulting fee; Merck: Consultant, Consulting fee; E. Dejesus, Gilead Sciences: Consultant, Investigator and Speaker's Bureau, Consulting fee and Speaker honorarium; Janssen: Consultant, Investigator and Speaker's Bureau, Consulting fee and Speaker honorarium; G. Crofoot, Gilead: Investigator and Scientific Advisor, Advisory honorarium and Research grant; ViiV: Investigator and Scientific Advisor, Advisory honorarium, Research grant and Research support; D. Ward, Gilead: Investigator, Research support; P. Benson, Gilead Sciences: Investigator, Shareholder and Speaker's Bureau, Research support and Speaker honorarium; ViiV Healthcare: Investigator, Research support; L. Wei, Gilead: Employee and Shareholder, Salary; K. White, Gilead Sciences, Inc.: Employee and Shareholder, Salary; S. Collins, Gilead: Employee and Shareholder, Salary; H. Martin, Gilead Sciences: Employee, Salary; A. Cheng, Gilead: Employee and Shareholder, Salary; E. Quirk, Gilead: Employee and Shareholder, Salary